All the places to go-- how will you know? : God has placed before you an open door. What will you do? - Ortberg, John. (Carol Stream, IL : Tyndale House Publishers, Inc., 2015)
In All the Places to Go ... How Will You Know?, bestselling author John Ortberg opens our eyes to the countless doors God places before us every day, teaches us how to recognize them, and gives us the encouragement to step out in faith and embrace all of the extraordinary opportunities that await. --Publisher's description.
Oh, the places you'll go! -- Open-door people and closed-door people -- No mo FOMO: overcoming the fear of missing out -- Common myths about doors -- Door #1 or door #2? -- How to cross a threshold -- What open doors will teach you about you -- The Jonah complex -- Thank God for closed doors -- The door in the wall.
Includes bibliographical references.
Keywords: Christian life